Efficacy and safety of long-term use of low molecular weight heparins in patients with systemic lupus erythematosus and antiphospholipid syndrome - N. V. Seredavkina; F. A. Cheldieva; A. A. Shumilova; T. M. Reshetnyak (Современная ревматология, 2023)
To date, the management of patients with antiphospholipid syndrome (APS) with ineffectiveness and/or intolerance to vitamin K antagonists and direct oral anticoagulants remains controversial. One of the treatment strategies is the administration of low molecular weight heparins (LMWH) over a long period of time.   Objective: to evaluate the efefficacy and safety of long-term treatment with LMWH in patients with APS.   Material and methods. The study included 15 patients (13 women and 2 men) with APS. In 2 of them APS was isolated, in 12 it was combined with systemic lupus erythematosus (SLE), and in 1 – with SLE and psoriatic arthritis. The mean age of patients was 44 ± 12 years, and the mean duration of disease was 12 [6; 18] years. All patients were repeatedly examined in the V. A. Nasonova Research Institute of Rheumatology during hospitalizations and continued outpatient care in the clinical diagnostic center of the Institute.   Results and discussion. Ten (67 %) patients received nadroparin, 5 (33 %) patients received enoxaparin. The median duration of therapy was 4 [1; 10] years. Indications for the use of LMWH were inefficacy and intolerance of oral anticoagulants (n = 12, 100 %) and vascular involvement such as thromboangiitis obliterans with the development of chronic arterial insufficiency, ulcers and necrosis of the toes (n = 6, 40 %). During therapy, 13 (86 %) of 15 patients showed clinical improvement: healing of ulcers and necrosis, reduction in the stage of arterial insufficiency, recanalization of venous blood clots. During the entire treatment period with LMWH, one patient experienced a relapse of thrombosis due to an insufficient dose of the drug. No hemorrhagic complications occurred in any case. Other adverse events, including elevated liver aminotransferases, osteoporosis, and thrombocytopenia, were also not observed.   Conclusion. The results obtained suggest that long-term therapy with LMWH may be safe and effective in patients with APS.